2010
DOI: 10.1177/0093854810362053
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Reading Complexity and Listening Comprehension of Canadian Police Cautions

Abstract: The reading complexity and listening comprehension of Canadian police cautions were measured. In Study 1, the complexity of 44 unique Canadian police cautions was assessed using five readability measures (Flesch-Kincaid reading level, sentence complexity, use of difficult words, use of infrequent words, and number of words). Results showed that 7 (37%) of the rightto-silence cautions (n = 19) and none of the right-to-legal-counsel cautions (n = 25) reached acceptable cutoff levels for all five measures. In Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Nevertheless, we believe that verifying understanding is sound practice because it allows interviewers to identify the aspects of the cautions that suspects do not understand and that are in need of explanation. Furthermore, our finding that the interviewers always explained the rights correctly on the few occasions when they attempted to explain the various rights contained in the cautions is encouraging because it appears that they understand the caution themselves and therefore have the ability to help suspects and accused persons to understand the information that is contained in an inherently complex caution (Eastwood, Snook, and Chaulk 2010).…”
Section: Discussionmentioning
confidence: 57%
“…Nevertheless, we believe that verifying understanding is sound practice because it allows interviewers to identify the aspects of the cautions that suspects do not understand and that are in need of explanation. Furthermore, our finding that the interviewers always explained the rights correctly on the few occasions when they attempted to explain the various rights contained in the cautions is encouraging because it appears that they understand the caution themselves and therefore have the ability to help suspects and accused persons to understand the information that is contained in an inherently complex caution (Eastwood, Snook, and Chaulk 2010).…”
Section: Discussionmentioning
confidence: 57%
“…Results showed that the students recalled, on average, 40% of their legal rights, and only 22% of the youths comprehended more than 50% of their rights. It should be noted that this issue is not unique to youth populations, as similar low levels of comprehension have been discovered with adult cautions as well (Cloud, Shepherd, NodvinBarkoff, & Shur, 2002: Eastwood, Snook, & Chaulk, 2010Fenner, Gudjonsson, & Clare, 2002;Gudjonsson, 1991).…”
mentioning
confidence: 84%
“…It is important to note its criterion for establishing grade levels is set at 75% or greater comprehension; typically one to two grades higher are needed for full (90% to 100%) comprehension (DuBay, 2004). The Flesch-Kincaid correlates well with standardized reading tests and is commonly used in Miranda-related research (e.g., Eastwood, Snook, & Chaulk, 2010;Helms, 2003Helms, , 2007 and the study of informed consent more generally (Paasche-Orlow, Taylor, & Brancati, 2003).…”
Section: Analysis Of Juvenile Miranda Warningsmentioning
confidence: 94%